2022
DOI: 10.3389/fimmu.2022.1007042
|View full text |Cite
|
Sign up to set email alerts
|

CAR-T manufactured from frozen PBMC yield efficient function with prolonged in vitro production

Abstract: Chimeric antigen receptor (CAR)-T cells are engineered to identify and eliminate cells expressing a target antigen. Current manufacturing protocols vary between commercial CAR-T cell products warranting an assessment of these methods to determine which approach optimally balances successful manufacturing capacity and product efficacy. One difference between commercial product manufacturing methods is whether T cell engineering begins with fresh (unfrozen) patient cells or cells that have been cryopreserved pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…In line with previous reports, [ 24 , 33 , 36 ] we found that cryopreserved PBMCs are associated with slower T-cell expansion ( Figure 5G-I ). IL-2 promotes the proliferation and differentiation of T cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous reports, [ 24 , 33 , 36 ] we found that cryopreserved PBMCs are associated with slower T-cell expansion ( Figure 5G-I ). IL-2 promotes the proliferation and differentiation of T cells.…”
Section: Discussionsupporting
confidence: 93%
“…These results partially supported that cryopreservation fully conserves activation, cytokine production and in vitro anti-tumor cytotoxicity in CAR-T cells, and mice antigen-specific T cells. [ 33 , 34 , 35 ] Since the T cells in our experiment were activated by non-specific stimulators (PMA and ionomycin), the effect of long-term cryopreservation on antigen-specific T cell response needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent source for the manufacturing of allogeneic CAR-Ts is PBMCs collected from healthy donors, where T-cells are isolated and expanded. This allows for the creation of multiple vials from a single apheresis product that can be easily used in a very rapid and standardized manufacturing protocol [9,10]. Another manner by which CAR-T can be manufactured is via isolation of stem cells from PBMCs [11], which can be further activated and transduced into CAR T-cells.…”
Section: Pbmcsmentioning
confidence: 99%
“…The viability of the cryopreserved CAR-T cells has been observed to be more than 50% upon thawing. CAR-T cells that have been cryopreserved can be kept and expanded again at a later date [ 85 ].…”
Section: Manufacturing and Infusion Of Car-t Cells For Cancer Treatmentmentioning
confidence: 99%